The diversification benefits within Islamic investments: the case of Malaysia-based Islamic equity investors
This article aims to assist Malaysia-based Islamic equity investors in identifying possible diversification benefits by diversifying their portfolio in the Southeast Asian market and the top 10 world’s largest equity markets (China, Japan, Hong Kong, India, UK, US, Canada, France, Germany and Switzerland). The multivariate GARCH-dynamic conditional correlation is applied to estimate the time-varying linkages of the selected Asian and international Islamic stock index returns with the Malaysian Islamic stock index returns, covering approximately eight years daily starting from 29 June, 2007 to 30 June, 2016. At the regional level, the results indicate that Malaysia-based Islamic equity investors would benefit most if they include the Japanese Islamic stock indices in their portfolio. Meanwhile, at the international level, the results imply that the US Islamic stock indices provide the most diversification benefit for the Malaysia-based Islamic equity investors.